Measuring Evolutionary Isolation for Conservation. - David W Redding (PLoS ONE, 2014)
Conservation planning needs to account for limited resources when choosing those species on which to focus attention and resources. Currently, funding is biased to small sections of the tree of life, such as raptors and carnivores. One new approach for increasing the diversity of species under consideration considers how many close relatives a species has in its evolutionary tree. At least eleven different ways to measure this characteristic on phylogenies for the purposes of setting species-specific priorities for conservation have been proposed. We find that there is much redundancy within the current set, with three pairs of metrics being essentially identical. Non-redundant metrics represent different trade-offs between the unique evolutionary history represented by a species verses its average distance to all other species. Depending on which metric is used, species priority lists can differ as much as 85% for the top 100 species. We call for some consensus on the theory behind these metrics and suggest that all future developments are compared to the current published set, and offer scripts to aid such comparisons.